2018
DOI: 10.31387/oscm0310203
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Intra-organisational Information Dependency: An Empirical Network Analysis of Vietnamese Freight Forwarding Industry

Abstract: The use of timely, accurate, and relevant information is crucial for supply chain performance. Within business firms, executives and managers depend on demand and inventory data to make decisions for business operations. In this technological era, many firms are reliant on technological platforms to share mission critical information between their business units to prevent bullwhip effect due to information lag, and to improve coordination and collaboration among the units. Extant literature reveals that there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…The study found a significant positive relationship between vendor management and practices adopted in quality management. Researchers believe organizations adopt and implement quality management practices to simplify supply chain management implementation (Teo, Dang-Pham, Nkhoma & Nguyen, 2018). Ryu, So and Koo (2009) explored the partnership and a firm's performance within the supply chain.…”
Section: Partnership Quality and Buyer Dependencementioning
confidence: 99%
“…The study found a significant positive relationship between vendor management and practices adopted in quality management. Researchers believe organizations adopt and implement quality management practices to simplify supply chain management implementation (Teo, Dang-Pham, Nkhoma & Nguyen, 2018). Ryu, So and Koo (2009) explored the partnership and a firm's performance within the supply chain.…”
Section: Partnership Quality and Buyer Dependencementioning
confidence: 99%